The Influence of Pricing Rate and Credit Procedures on Home Purchase Decisions with Purchase Intention as a Mediating Variable (Case Study of Pt. Bank Cimb Niaga Bogor Branch) - Alexander Bagus Lowu; Bernard T. Widjaja; Jimmy Lizardo (PT. Anagata Sembagi Education, 2024)
This study investigates the impact of pricing rates and credit procedures on home purchase decisions, focusing on PT Bank CIMB Niaga Bogor Branch, with purchase intention serving as a mediating variable. Through empirical analysis and discussion, several key findings emerge. Firstly, pricing rates significantly influence home purchase decisions, indicating that competitive pricing strategies attract potential buyers. Secondly, efficient credit procedures positively affect purchase decisions by facilitating smoother transaction processes for consumers. Additionally, both pricing rates and credit procedures independently contribute to enhancing purchase intention among buyers. Importantly, purchase intention plays a critical role as it mediates the relationship between pricing rates, credit procedures, and final purchase decisions. These findings underscore the interconnectedness of pricing strategies, credit facilitation, purchase intention, and actual purchase behavior in the housing finance sector, providing valuable insights for strategic decision-making in banking institutions.